IMPLEMENTASI SISTEM KONTROL OTOMATIS PADA PROTOTIPE ALAT PENERANGAN JALAN BERBASIS INTERNET OF THINGS SEBAGAI UPAYA EFISIENSI ENERGI DI JALAN BUKIT DHARMA RAYA JIMBARAN (Jurnal SPEKTRUM, 2025)
The implementation of an AC Light Dimmer and Relay 2 Channel as an automatic lamp control system on a Street Lighting (APJ) prototype based on the Internet of Things (IoT) is used to support energy efficiency on Jalan Bukit Dharma Raya Jimbaran. This system is designed to automatically adjust light intensity based on time and the presence of road users detected by an ultrasonic sensor. Monitoring and control are performed in real-time via the Telegram platform, with energy consumption monitored using the PZEM-004T module. The prototype is built using an ESP32 microcontroller, which controls the lamp activation, brightness through the AC Light Dimmer, and ON/OFF status via the Relay 2 Channel. Test results show that the system can improve energy efficiency by up to 43.75% and save electricity costs by Rp132.56 during 2 hours of operation. This system implementation has proven to be effective, adaptive to environmental conditions, and supports the application of intelligent and energy-efficient street lighting systems.